Stable oxygen isotope ratios of diatoms and relative species abundances in ODP Site 145-882 - George E A Swann (PANGAEA, 2010)
Recent research has increasingly advocated a role for the North Pacific Ocean in modulating global climatic changes over both the last glacial cycle and further back into the geological record. Here a diatom d18O record is presented from Ocean Drilling Program Site 882 over the Pliocene/Quaternary boundary from 2.73 Ma to 2.52 Ma (MIS G6–MIS 99). Large changes in d18Odiatom of c. 4 per mil from 2.73 Ma onwards are documented to occur on a timeframe broadly coinciding with glacial–interglacial cycles. These changes are primarily attributed to large scale inputs of meltwater from glacials surrounding the North Pacific Basin and the Bering Sea. Despite these inputs and associated change in surface water salinity, on the basis of existing opal and UK37 temperature data and new modelled water column densities, no evidence exists to suggests a removal of the halocline stratification or a resumption of the high productivity system similar to that which prevailed prior to 2.73 Ma. The permanence of the halocline suggests that the region played a key role in driving global climatic changes over the early glacial–interglacial cycles that followed the onset of major Northern Hemisphere Glaciation by inhibiting deep water upwelling and ventilation of CO2 to the atmosphere.
Supplement to: Swann, GEA (2010): Salinity changes in the North West Pacific Ocean during the late Pliocene/early Quaternary from 2.73 Ma to 2.52 Ma. Earth and Planetary Science Letters, 297(1-2), 332-338, https://doi.org/10.1016/j.epsl.2010.06.035